The Private sector and Nigeria's agricultural development - Osuntogun, C. Adeniyi; Ugorji, Shedrack Rex Uzo.; Agricultural and Rural Management Training Institute (Ilorin, Nigeria) (Ilorin : Agricultural and Rural Management Training Institute, 1984)
The papers in this volume are selected from those read at the Seminar on the Role of Private Sector in Nigerian agriculture. They are grouped into five main parts: Part one focuses on the role of the private sector in Nigeria's agricultural development; chapter 2 discusses the participation of the private enterprise sector in the improvement of the agricultural sector. Part 2 is concerned with experiences and case studies of private sector participation in agricultural Development in Nigeria.
Selected papers from the First ARMTI National Seminar on the Role of the Private Sector in Nigerian Agriculture, held Oct. 17-19, 1983, organized by Agricultural and Rural Management Training Institute.
Includes bibliographical references.
osc 29/01/2019
Loans
Keywords: Agriculture